2011
DOI: 10.1111/j.1365-2141.2011.08726.x
|View full text |Cite
|
Sign up to set email alerts
|

Attainment of complete/very good partial response following rituximab‐based therapy is an important determinant to progression‐free survival, and is impacted by polymorphisms in FCGR3A in Waldenstrom macroglobulinaemia

Abstract: SummaryThe incorporation of rituximab into various regimens has improved depth of response in Waldenstrom macroglobulinaemia (WM), though the impact of achieving better responses remains to be determined. We examined response depth on progression-free survival (PFS) in 159 rituximab-naïve WM patients who received rituximab-based therapy. The median follow-up was 33AE5 months, and categorical responses were as follows: complete response (CR, 8AE8%); very good partial response (VGPR, 13AE2%); partial response (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 54 publications
4
44
0
Order By: Relevance
“…The quality of response to primary therapy may be associated with survival in lymphoproliferative disorders. In patients with WM, the depth of the response may be associated with longer PFS, 30 which is what we also observed in our study, however, several years of follow-up are needed to evaluate the effect of the therapy and the quality of response on survival. Future clinical studies should aim at the development of regimens with higher CR rates and reasonable toxicity.…”
Section: Discussionsupporting
confidence: 83%
“…The quality of response to primary therapy may be associated with survival in lymphoproliferative disorders. In patients with WM, the depth of the response may be associated with longer PFS, 30 which is what we also observed in our study, however, several years of follow-up are needed to evaluate the effect of the therapy and the quality of response on survival. Future clinical studies should aim at the development of regimens with higher CR rates and reasonable toxicity.…”
Section: Discussionsupporting
confidence: 83%
“…5,10 The attainment of VGPR/CR is of particular interest given the association of longer PFS in WM patients receiving a rituximabcontaining regimen, including proteasome inhibitor therapy. 5,9,10 Consistent with this finding, patients on this study who attained at least a VGPR during the follow-up period demonstrated longer PFS vs patients who attained a minor or partial response. With a median follow-up of 15.4 months, 64% of patients remained free of disease progression, and a longer follow-up will invariably be required to establish the relative PFS for CaRD vs BDR, in which PFS of 42 months to .4 years have been reported.…”
Section: Org Fromsupporting
confidence: 71%
“…Reasons (multiple causes can apply) for treatment initiation based on WM consensus criteria were symptomatic anemia (n 5 30), extramedullary disease (n 5 5), hyperviscosity (n 5 4), and IgM-related PN (n 5 3). The median number of treatment cycles administered including induction and maintenance was 12 (range, [4][5][6][7][8][9][10][11][12][13][14]. Ten patients completed all 14 cycles of planned induction and maintenance therapy, and 8 patients are currently receiving maintenance therapy.…”
Section: Patients and Disease Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Improved progressionfree survival in association with attainment of a molecular response has been described in multiple studies in patients with follicular lymphoma in which there is a disease-related genetic marker (BCL2/ IgH fusion transcript), as well as for myeloma using tumor-related IgH rearrangements for quantitative PCR analysis. [24][25][26][27][28][29][30] Quantitative PCR analysis of BM cells for BCL2/IgH at baseline also served as a prognostic indicator for response and disease control, 24 and a similar study using AS-PCR for MYD88 L265P could also help establish its worthiness as a prognostic marker for WM.…”
Section: Discussionmentioning
confidence: 99%